Phytochemical Screening and Biological Studies of Shilajit (Asphaltum) - Shahid Aziz; Sidra Khaliq; Habib ur-Rehman; Kh. Shakeel Ghani; Muhammad Irshad; Ivan R Green; Hidayat Hussain (International Journal of Phytomedicine, 2017)
Shilajit (asphaltum) is produced by the long term humification of dead plant material and organic vegetable matter by different micro-organisms and has great potential for the treatment of a variety of human conditions. This treatise reviews its origin, sources, chemical composition, biological and commercial importance. Phytochemical analysis was done by standard methods to evaluate different Shilajit (asphaltum) classes of compounds in different samples of shilajit which are responsible for their biological activity. Shilajit`s anti-microbial activity has been evaluated against four different bacterial strains viz., Escherichia coli, Psuedomonas aeuroginosa, Klebisella pneumonia and Staphylococcus aureus. Phytochemical analysis illustrated that shilajit contains terpenoids, cardiac glycosides, saponins and reducing sugars. Surprisingly, some classes of compounds are absent in shilajit viz., alkaloids, flavonoids, tannins and anthraquinones. . Shilajit showed no response towards halophytic bacteria and negligible activity was shown towards other strains of bacteria. Since anti-microbial activity is based on environmental factors its activity varied between locations.